The Role of Procalcitonin Test in the Diagnosis of Bacterial Infections in Rheumatic Diseases - B. S. Belov; G. M. Tarasova; N. V. Muravyova (Антибиотики и Химиотерапия, 2020)
The problem of differential diagnosis of a bacterial infection and an active rheumatic process still retains its relevance in modern rheumatology. It is very important to search for a biomarker - the gold standard for diagnosis of infection in patients with rheumatic diseases (RD) in order to quickly determine the treatment tactics. This review analyzes the diagnostic significance and the possibility of using the procalcitonin test (PCT) for the diagnosis of bacterial infections in modern rheumatology. When interpreting PCT values, it is necessary to take into account the specific rheumatic nosology, as well as the full range of clinical, laboratory, and instrumental data.